Efeitos da crioterapia em marcadores bioquímicos, histológicos e funcionais após a compressão do nervo isquiático em ratos - Duarte, Bárbara Santos Luccas (2018)
Peripheral nerves are responsible for conducting sensory information from skin, muscles and other organs to the central nervous system (CNS) and motor information from the CNS to somatic muscles and effector organs controlled by the autonomic system. The occurrence of peripheral neural lesions can lead to functional and motor impairment in the neural territories involved. Cryotherapy is a therapeutic technique extensively used as a form of analgesia. However its effects on experimental animal models of peripheral neural compression are poorly studied. The present study aimed to evaluate the effects of cryotherapy on oxidative stress and behavioral sensorial or painful motor changesafter a sciatic nerve compression injury in rats. The animals were firstly submitted to the von Frey test. After 72 hours the groups Peripheral Nerve Lesion (PNL), PNL + Cryo (Cryo) and Sham were submitted to surgical sciatic nerve compression or surgery simulated. After 24 hours, the 20-minute cryotherapy treatment was started once a day for 15 days in all groups, with the exception of the Control and Sham Group. The tests were repeated in 7 and 15 days after treatment. On the 15th day the the animals were euthanized and samples of blood and muscle tissue collected for analysis, oxidative stress and damage markers. The results demonstrate that cryotherapy was able to improve the sciatic function of rats subjected to nerve damage at the day7. In addition, through biochemical tests, we demonstrated that the lesion increased oxidative damage and cryotherapy was able to attenuate these levels.